Hey im currenty suck on this question:
3^x+2 = 2^1-x
Well so far ive got
x+2 log3 = 1-x log 2
but im not sure where to go from there
1) Expand the brackets
$\displaystyle xlog(3) + 2log(3) = log(2) - xlog(2)$
2) add $\displaystyle xlog(2)$ and subtract $\displaystyle 2log(3)$ to both sides
$\displaystyle xlog(3) + xlog(2) = log(2) - 2log(3)$
3)This simplifies to
$\displaystyle xlog(6) = log(2) - log(9)$
4)Divide both sides by log(6)
$\displaystyle x = \frac{log(2) - log(9)}{log(6)}$
and there we go